Efficacy and cost-effectiveness of Internet-based selective eating disorder prevention: study protocol for a randomized controlled trial within the ProHEAD Consortium$Stephanie Bauer, Sally Bilić, Christina Reetz, Fikret Ozer, Katja Becker, Heike Eschenbeck, Michael Kaess,Christine Rummel-Kluge, Hans-Joachim Salize, Silke Diestelkamp, Markus Moessner and the ProHEAD Consortium - Bauer, Stephanie; Bilić, Sally Sophie; Reetz, Christina; Özer, Fikret; Kaess, Michael; Salize, Hans Joachim; Moessner, Markus (Trials, 2019)
The development of efficacious, cost-effective, and widely accessible programs for the prevention of eating disorders (EDs) is crucial in order to reduce the ED-related burden of illness. Programs using dissonance-based and cognitive behavioral approaches are most effective for the selective prevention of ED. Internet-based delivery is assumed to maximize the reach and impact of preventive efforts. However, the current evidence for Internet-based ED prevention is limited. The present trial evaluates the efficacy and cost-effectiveness of two new interventions (based on dissonance theory and principles of cognitive behavioral therapy (CBT)) that are implemented as add-ons to the existing Internet-based ED prevention program ProYouth.